Quantification of microbial cells and virus-like particles in the water column above Kermadec Trench - Clemens Schauberger; Mathias Middelboe; Ronnie N Glud (PANGAEA, 2024)
Water samples were collected using 7.5-Liter Niskin bottles and fixed with 25% electron microscopy graded glutaraldehyde (1% final concentration) and stored at -80°C until quantification by flow cytometry. Samples were measured in triplicates using a BD FACSCanto™ II flow cytometer, after staining with SYBR Green I (Brussaard 2004). The flow rate was 5–7 μl/min, as determined by BD Trucount™ Beads. The laser settings and gating examples can be found in the Supporting Information of Schauberger et al. (2021).